Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 30



Work Step by Step

$\frac{(x^{2})^{8}x}{x^{9}}=\frac{x^{2\times8}\times x}{x^{9}}=\frac{x^{16}\times x}{x^{9}}=\frac{x^{16+1}}{x^{9}}=\frac{x^{17}}{x^{9}}=x^{17-9}=x^{8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.